2015
DOI: 10.1111/imj.12768
|View full text |Cite
|
Sign up to set email alerts
|

Conditions associated with extreme hyperferritinaemia (>3000 μg/L) in adults

Abstract: Extreme hyperferritinaemia greater than 3000 μg/L is uncommon in adult patients. The highest serum ferritin values are seen in HLH, but the differential diagnosis for serum ferritin greater than 3000 μg/L remains broad with iron overload and liver disease being the most common causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
0
21
1
Order By: Relevance
“…Serum ferritin and CRP concentrations correlated with the severity of acute toxicity and declined in response to tocilizumab or corticosteroids; however, additional data are needed to determine their utility in monitoring the response to CRS therapy. Severe hyperferritinemia (> 20,000 ng/ml) is not typically observed in infections even in heavily transfused patients (24) and could serve as a useful tool in distinguishing sCRS from other causes of fever after CAR-T cell infusion. Serum concentrations of IL-6 and IFN-γ also correlated with the severity of toxicity and had predictive value, with high concentrations within 1 day after CAR-T cell infusion identifying patients who subsequently developed severe neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Serum ferritin and CRP concentrations correlated with the severity of acute toxicity and declined in response to tocilizumab or corticosteroids; however, additional data are needed to determine their utility in monitoring the response to CRS therapy. Severe hyperferritinemia (> 20,000 ng/ml) is not typically observed in infections even in heavily transfused patients (24) and could serve as a useful tool in distinguishing sCRS from other causes of fever after CAR-T cell infusion. Serum concentrations of IL-6 and IFN-γ also correlated with the severity of toxicity and had predictive value, with high concentrations within 1 day after CAR-T cell infusion identifying patients who subsequently developed severe neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In 83 patients identified with SF levels >3000 μg/l at a teaching hospital in Vancouver, 21 cases (25%) were due to transfusional iron overload, 16 (19%) due to liver disease and 15 (18%) due to mixed factors. HLH was diagnosed in 6 patients (7%) (Wormsbecker et al , ). Finally, a study of markedly elevated SF levels ≥10 000 μg/l in patient samples analysed over a 12‐month period in a district general hospital biochemistry laboratory revealed 23 cases, with an incidence of 0·08% of SF requests: malignancy accounted for 6/23 cases, liver disease 5, transfusion or thalassaemia 5 and infections 4 (Crook & Walker, ).…”
Section: Raised Serum Ferritin Levels (Hyperferritinaemia)mentioning
confidence: 99%
“…The 6 easily measured criteria are each sensitive for pathologic immune activation in adults, but very nonspecific in and of themselves. For example, extreme hyperferritinemia has traditionally been thought to be quite specific for HLH, 4 but recent studies have shown that ferritin levels of 3000 mg/L or higher, 5 and even of 50 000 mg/L or higher, 6 are not predictive for adult HLH. The most common conditions associated with extreme hyperferritinemia in these studies included liver disease, renal failure, and transfusional iron overload, whereas HPS/HLH made up only 7% (6/83) 5 and 20% (22/111) 6 of the respective cohorts.…”
Section: Introductionmentioning
confidence: 99%